Crystal structure and magnetic properties of R11Co4In9 (R=Tb, Dy, Ho and Er) compounds. (March 2021) - Baran, S.; Tyvanchuk, Yu.; Szytuła, A.
Abstract: Crystal structure and magnetic properties of the R11 Co4 In9 compounds (R = Tb–Er) have been investigated by means of X-ray diffraction as well as dc magnetic measurements. The compounds crystallize in the orthorhombic Nd11 Pd4 In9 -type crystal structure ( Cmmm space group) in which the rare earth atoms occupy five nonequivalent sublattices. Magnetic properties of the investigated compounds are related mainly to the R 3+ ions. The values of effective magnetic moments in the paramagnetic state are close to the free R 3+ ion values while the moments in the ordered state at T = 2.0 K (R = Tb, Dy) or T = 1.9 K (R = Ho, Er) and H = 90 kOe are lower than the respective R 3+ moments. The compounds show complex magnetic properties below 95 K (Tb), 88 K (Dy), 35 K (Ho) and 5.4 K (Er). With increase of temperature the antiferromagnetic ground state changes to the ferro- or ferrimagnetic one. The critical temperatures of magnetic ordering do not fulfill the de Gennes scaling indicating a strong influence of the crystal electric field (CEF) in stabilizing the magnetic order. Highlights: Crystal structure and magnetic data for R11Co4In9 (R = Tb–Er) are reported. The compounds crystallize in the orthorhombic Nd11Pd4In9-type structure. Magnetic data indicate antiferromagnetic ground state. With increasing temperature a change of magnetic properties is observed.